Accumulated dry matter and grain yield in flooded hybrid rice simulated with the SimulArroz model - Ribas, Giovana Ghisleni; Streck, Nereu Augusto; Lago, Isabel; Zanon, Alencar Junior; Waldow, Daniel Arthur Gaklik; Duarte Junior, Ary José; Nascimento, Moisés de Freitas do; Fontana, Vanessa (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the calibration and the performance of the SimulArroz model for simulating the accumulated dry matter and the grain yield of flooded hybrid rice cultivars in the state of Rio Grande do Sul, Brazil. The experiments were carried out in a completely randomized block design in the municipalities of Santa Maria, Cachoeirinha, Santa Vitória do Palmar, Uruguaiana, Bagé, Camaquã, and Cachoeira do Sul. In Santa Maria and Cachoeirinha, the shoot dry matter accumulation and grain yield of three hybrid cultivars (Prime CL, Inov CL, and QM 1010 CL) and one conventional rice cultivar, used as control (Irga 424), were evaluated. In the other sites, only grain yield was evaluated. It was observed that more photoassimilates from the culm shoots are allocated in the hybrid cultivars, in order to sustain a greater panicle, compared with conventional rice. The calibration of the SimulArroz model used is efficient to simulate the accumulated dry matter and grain yield of hybrid rice cultivars in flooded rice crop regions of the state of Rio Grande do Sul.